Wage distributions by wage-setting regime - Knut Gerlach; Gesine Stephan (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2005)
Collective wage contracts impose restrictions on wage-setting. We utilize German linked employer-employee data for blue-collar worker to compute the dispersion of wages and wage components within and across firms under three different wage-setting regimes: Establishments applying sectoral collective contracts, establishments with firm-level contracts and uncovered establishments. The empirical analysis confirms a lower dispersion of wages and wage components for firms applying sectoral collective contracts compared to companies in the other two wage-setting regimes. Implications for policy are discussed.
Keywords: J31; J51; 330; Lohnstruktur; Tarifvertrag; Firmentarifvertrag